FUNGSI UME KBUBU DAN AKTIVITAS PENGHUNINYA SAAT CUACA DINGIN DI DESA BINAUS, KABUPATEN TIMOR TENGAH SELATAN – NUSA TENGGARA TIMUR - Puspita, Dhanang; Tauho, Kristiani D.; Nusawakan, Arwyn W.; Kinasih, Angkit (KRITIS, 2016)
The natural climate of Nusa Tenggara Timur (NTT) is dry all the year. However, prior to wet season, the region will suffer from cold weather, particularly in August. Ume kbubu and ume naek, both are traditional houses of Timorese especially for those who come from Mollo. Ume kbubu is used as a kitchen and barn, while ume naek is used for shelter and receiving guests. This paper will explain the functional change of ume kbubu during cold weather. The research took place at Binaus village, Timor Tengah Selatan district in August 2016 using observation to monitor the people’s activity. Measurement of the temperature was conducted for 24 hours. At night the temperature outside might reach 20°C, and 22°C in ume naek, while in ume kbubu, it can reach 35 - 37°C. The low temperature, both outside and in ume naek, causing the residents to replace their activities in the warm ume kbubu. By evening, the people are usually sleeping in ume naek, but in cold weather, they sleep at ume kbubu. The conclusion of this research is there was a functional change of ume kbubu in the community activity during cold weather